Experimental evaluation of the impact of low tesla transverse magnetic field on dose distribution in presence of tissue interfaces. (September 2018) - Cusumano, Davide; Teodoli, Stefania; Greco, Francesca; Fidanzio, Andrea; Boldrini, Luca; Massaccesi, Mariangela; Cellini, Francesco; Valentini, Vincenzo; Azario, Luigi; De Spirito, Marco
Abstract: Purpose: Aim of this study is to experimental evaluate the impact of a 0.35 T transverse magnetic field on dose distribution in presence of tissue-air and tissue-lung interfaces. Methods: The investigation was carried out using MRIdian (ViewRay, Cleveland, Ohio) and it consisted of comparing experimental measurements performed by Gafchromic EBT3 film dosimetry, to Montecarlo simulations, carried out in the presence and, as well as, the absence of the magnetic field. A preliminary dose calibration was planned on MRIdian, arranging 3 × 3 cm 2 film pieces in a water slab phantom and exposing them at different beam-on times, in a dose range equal to 0.1–12.1 Gy. All experimental measurements were then carried out using the calibrated films and delivering one single beam orthogonally to three different phantoms: without inhomogeneity, with an air gap and with a lung inhomogeneity. The dose distributions measured by EBT3 films in presence of magnetic field were compared to those calculated in the presence and, as well as, the absence of the magnetic field, in terms of gamma analysis. A quantification of electron return effect (ERE) was also performed. Results: All the tested plans considering the magnetic field show a gamma-passing rate higher than 98% for 3%/3 mm gamma analysis. In presence of tissue-air interface, the electron return effect causes an over-dosage of +31.9% at the first interface and an under-dosage of −33% at the second interface. The dosimetric variations in presence of tissue-lung interface results to be smaller (+0.8% first interface, −1.3% second interface). Conclusion: The impact of 0.35 T magnetic field is not negligible and it can be effectively modelled by the Montecarlo dose calculation platform available in the MRIdian TPS.